Two cinnamoyl hydroxamates as potential quorum sensing inhibitors against Pseudomonas aeruginosa - Pan, Deng; Wu, Hua; Li, Jun-Jian; Wang, Bo; Jia, Ai-Qun (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionPseudomonas aeruginosa is a ubiquitous pathogen that causes various infectious diseases through the regulation of quorum sensing (QS). The strategy of interfering with the QS systems of P. aeruginosa, coupled with a reduction in the dosage of conventional antibiotics, presents a potential solution to treating infection and mitigating antibiotic resistance. In this study, seven cinnamoyl hydroxamates were synthesized to evaluate their inhibitory effects on QS of P. aeruginosa. Among these cinnamic acid derivatives, we found cinnamoyl hydroxamic acid (CHA) and 3-methoxy-cinnamoyl hydroxamic acid (MCHA) were the two most effective candidates. Furtherly, the effect of CHA and MCHA on the production of virulence factors and biofilm of P. aeruginosa were evaluated. Ultimately, our study may offer promising potential for treating P. aeruginosa infections and reducing its virulence.MethodsThe disc diffusion test were conducted to evaluate inhibitory effects on QS of seven cinnamoyl hydroxamates. The influence of CHA and MCHA on the production of virulence and flagellar motility of P. aeruginosa was furtherly explored. Scanning electron microscopy (SEM) experiment were conducted to evaluate the suppression of CHA and MCHA on the formed biofilm of P. aeruginosa. RT-qPCR was used to detect rhlI, lasA, lasB, rhlA, rhlB, and oprL genes in P. aeruginosa. In silico docking study was performed to explore the molecular mechanism of CHA and MCHA. The synergistic effects of CHA with gentamicin were detected on biofilm cell dispersal.ResultAfter treatment of CHA or MCHA, the production of multiple virulence factors, including pyocyanin, proteases, rhamnolipid, and siderophore, and swimming and swarming motilities in P. aeruginosa were inhibited significantly. And our results showed CHA and MCHA could eliminate the formed biofilm of P. aeruginosa. RT-qPCR revealed that CHA and MCHA inhibited the expression of QS related genes in P. aeruginosa. Molecular docking indicated that CHA and MCHA primarily inhibited the RhlI/R system in P. aeruginosa by competing with the cognate signaling molecule C4-HSL.Additionally, CHA exhibited potent synergistic effects with gentamicin on biofilm cell dispersal.DiscussionP. aeruginosa is one of the most clinically and epidemiologically important bacteria and a primary cause of catheter-related urinary tract infections and ventilator-associated pneumonia. This study aims to explore whether cinnamoyl hydroxamates have inhibitory effects on QS. And our results indicate that CHA and MCHA, as two novel QSIs, offer promising potential for treating P. aeruginosa infections and reducing its virulence.